PENGARUH REKRUTMEN DAN SELEKSI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. PLN (PERSERO) UIWS2JB ULP LEMBAYUNG UP3 KABUPATEN LAHAT - Emila Sholiha (Jurnal Manajemen dan Bisnis, 2021)
The purpose of this study is to determine the effect of recruitment and selection on products to determine the effect of recruitment on employee productivity at PT. PLN (Persero) UIWS2JB ULP Lembayung UP3 Lahat RegencyThis study uses a quantitative approach because the data obtained using numbers and statistical analysis using multiple linear regression.The results of the t test show that the significance value of the Recruitment variable (X1) is smaller than the real level (0.000 <0.05), which means that the Recruitment variable has a significant effect on Work Productivity. The value of the t test results shows that the significance value of the Selection variable (X2) is smaller than the real level (0.006 <0.05), which means that the Selection variable has a significant effect on Work Productivity. And the value of the F test results shows that the significance value is smaller than the real level (0.000 < 0.05), which means that the Recruitment (X1) and Selection (X2) variables together have a significant effect on Employee Work Productivity at PT. PLN (Persero) UIWS2JB ULP Lembayung UP3 Lahat Regency.